The Catalan Epistemic Modal Marker “Pot molt ben ser”: from Emphatic Possibility to High Probability - Mar Massanell i Messalles (Catalan Journal of Linguistics)
In this article I deal with the Catalan epistemic marker pot molt ben ser ‘it may very well be’, which expresses high confidence on the part of the speaker in the truth value of the propositional content of his utterance. I start by extracting examples of the construction from the CICA, CIVAL and CTILC computerized corpora, and then analyse them within the framework of the Invited Inference Theory of Semantic Change (Traugott & Dasher 2002). Grammaticalization begins in contexts in which the modal periphrasis with poder ‘can, may/might’ as auxiliary and ésser ‘be’ as main verb is intensified with the interpolation of the adverb ben ‘well’, the resulting construction serving as an expressive resource to defend the existence of a previously denied possibility. Through bridge contexts that allow the interlocutor to infer that the speaker values the propositional content of his statement as not only possible but even probable, as happens when the emphatic expression is intended to reinforce a neutral one, or when it is accompanied by a causal clause that gives it inferential value, the conventionalization of the high probability meaning eventually comes about.